STRATEGI MEGHIDUPKAN LITERASI AWAL ANAK USIA DINI RENTANG USIA NOL SAMPAI LIMA TAHUN - Latif Latif (Program Studi Pendidikan Guru PAUD Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2019)
Literacy is currently very important in life. However, the problem of Indonesian children's literacyability is far from what was expected. It caused by parents have not been able to be a good model of literation.Therefore, the strategies need to be applied to improve early childhood literacy. This study uses qualitativeresearch using theoretical studies. Improving of early childhood literacy of parents can do activities that canbe done such as activities at home and their surrounding. Activities at home can be done such as readingwhen they are sleeping, eating and drinking, bathing and playing. And, the activities in their environment canbe done by introducing the library and providing book shopping.